Segmentacja produktów i odbiorców jako narzędzie controllingu sprzedaży - Dyczkowska, Joanna (Segmentation of products and customers as an instrument of sales controlling, 2006)
The paper focuses on pointing out and characterizing selected methods of classification of products and customers by controllers. The author presents various criteria of segmentation like profit margin, total value of purchase, frequency of orders and regularity in amounts ordered. The article emphasizes importance of evaluation of clients in terms of punctuality in payments as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 29-37